Study of the Special Programmes for Girls’ Education - Planning Commission (Planning Commission, 1978)
It was observed that there had been gradual but progressive increase in the enrolments of the girls over the plan periods and that the gap in the education of boys and girls appears to have been narrowing down during the last two decades. At the end of 1977-78, 68.0 per cent of the girls in the age group 6-11 years reported to have attended primary schools as against 32.4 per cent at the end of the First Plan. However, great disparity in the progress of girls' education among the States is still noticeable.
Programme Evaluation Organisation Planning Commission Government of India